Structural insights into selective agonist actions of tamoxifen on human Estrogen Receptor alpha - Chakraborty, Sandipan (J Mol Model, 2014)
Tamoxifen, an anti-estrogenic ligand in breast tissues and being used as a first-line treatment in ER-positive breast cancers, is found to develop resistance followed by resumption of growth of the tumor in about 30% of cases. Whether tamoxifen starts assisting in proliferation in such cases or there exists any ligand-independent pathways to transcription is not fully understood; also, no ERα mutants have been detected so far which could lead to tamoxifen resistance. Performing in-silico conformational analysis of ERα ligand binding domain, in the absence and presence of selective agonist (Diethylstilbestrol; DES), antagonist (Faslodex; ICI), and SERM (4-hydroxy tamoxifen; 4-OHT) ligands, we elucidated ligand-responsive structural modulations of ERα-LBD dimer in their agonist and antagonist complexes and address the issue of “tamoxifen resistance”. We found DES and ICI to stabilize the dimer in their agonist and antagonist conformations, respectively. The ERα-LBD dimer without the presence of any bound ligand also leads to a stable structure in agonist conformation. However, the binding of 4-OHT to antagonist structure is found to lead to a flexible conformation allowing the protein visiting conformations populated by agonists as are evident from principal component analysis and radius of gyration plots. Further, the relaxed conformations of the 4-OHT bound protein is found to exhibit a diminished size of the co-repressor binding pocket at LBD, thus signaling a partial blockage of the co-repressor binding motif. Thus, the ability of 4-OHT bound ERα-LBD to assume flexible conformations visited by agonists and reduced co-repressor binding surface at LBD provide crucial structural insights into tamoxifen-resistance complementing our existing understanding.